A phase I study of the PD-L1 inhibitor, durvalumab, in combination with a PARP inhibitor, olaparib, and a VEGFR1–3 inhibitor, cediranib, in recurrent women's cancers with biomarker analyses. Issue 1 (25th July 2019) - Zimmer, Alexandra S.; Nichols, Erin; Cimino-Mathews, Ashley; Peer, Cody; Cao, Liang; Lee, Min-Jung; Kohn, Elise C.; Annunziata, Christina M.; Lipkowitz, Stanley; Trepel, Jane B.; Sharma, Rajni; Mikkilineni, Lekha; et al.
Abstract : Background: Strategies to improve activity of immune checkpoint inhibitors are needed. We hypothesized enhanced DNA damage by olaparib, a PARP inhibitor, and reduced VEGF signaling by cediranib, a VEGFR1–3 inhibitor, would complement anti-tumor activity of durvalumab, a PD-L1 inhibitor, and the 3-drug combination would be tolerable. Methods: This phase 1 study tested the 3-drug combination in a 3 + 3 dose escalation. Cediranib was taken intermittently (5 days on/2 days off) at 15 or 20 mg (dose levels 1 and 2, respectively) with durvalumab 1500 mg IV every 4 weeks, and olaparib tablets 300 mg twice daily. The primary end point was the recommended phase 2 dose (RP2D). Response rate, pharmacokinetic (PK), and correlative analyses were secondary endpoints. Results: Nine patients (7 ovarian/1 endometrial/1 triple negative breast cancers, median 3 prior therapies [2–6]) were treated. Grade 3/4 adverse events include hypertension (1/9), anemia (1/9) and lymphopenia (3/9). No patients experienced dose limiting toxicities. The RP2D is cediranib, 20 mg (5 days on/2 days off) with full doses of durvalumab and olaparib. Four patients had partial responses (44%) and 3 had stable disease lasting ≥6 months, yielding a 67% clinical benefit rate. No significant effects on olaparib or cediranib PK parameters from the presence of durvalumab, or the co-administration of cediranib or olaparib were identified. Tumoral PD-L1 expression correlated with clinical benefit but cytokines and peripheral immune subsets did not. Conclusions: The RP2D is tolerable and has preliminary activity in recurrent women's cancers. A phase 2 expansion study is now enrolling for recurrent ovarian cancer patients. Trial registration: ClinicalTrials.gov identifier: NCT02484404 . Registered June 29, 2015.